Boosting Backward Search Throughput for FM-Index Using a Compressed Encoding - Herruzo-Ruiz, José Manuel; González-Navarro, Sonia; Ibáñez, Pablo; Viñals, Victor; Alastruey-Benedé, Jesús; Plata-González, Óscar Guillermo (My University, 2019)
The rapid development of DNA sequencing technologies has demanded for com- pressed data structures supporting fast pattern matching queries. FM-index is a widely-used compressed data structure that also supports fast pattern matching queries. It is common for the exact matching algorithm to be memory bound, resulting in poor performance. Searching several symbols in a single step improves data locality, although the memory bandwidth requirements remains the same. We propose a new data-layout of FM-index, called Split bit-vector, that compacts all data needed to search k symbols in a single step (k-step), reducing both memory movement and computing requirements at the cost of increasing memory footprint.
Keywords: ADN - Análisis secuencial; ADN